Analysis of Internal Audit Effectiveness in Government Assistance Program X Using the Management Control Systems Framework (E-Jurnal Akuntansi, 2026)
Internal audit plays an important role in ensuring the effectiveness of government assistance programs, particularly in achieving accountability and target accuracy. However, audit findings indicate several weaknesses in its implementation. This study aims to analyze the effectiveness of internal audit using the Management Control Systems framework. A descriptive qualitative approach with a case study method was employed, using in-depth interviews and document analysis. The analysis was based on the dimensions of result control, action control, personnel control, and cultural control. The findings show that the internal audit system has comprehensive control structures, but its implementation is not yet optimal. Performance measurement remains output-oriented, action control tends to be bureaucratic, auditor capacity is limited, and value internalization is uneven. Overall, internal audit effectiveness is moderately effective but requires improvement in outcome orientation, control flexibility, auditor competence, and organizational culture.
Keywords: Internal Audit; Effectiveness; Management Control Systems; Public Sector